2010
DOI: 10.1007/s10695-010-9453-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses of antioxidant enzymes, lipid peroxidation, and Na+/K+-ATPase in liver of the fish Goodea atripinnis exposed to Lake Yuriria water

Abstract: Lake Yuriria, located in the heavily populated and polluted Mexican Central Plateau, receives domestic sewage, industrial effluents, and municipal wastewaters that are still directly discharged without treatment into the tributaries and the lake. Pollutants in water and sediments include heavy metals, aromatic hydrocarbons, and organochlorine pesticides. Activities of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), as well as Na⁺/K⁺-adenosine triphosphatase (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 58 publications
4
17
0
4
Order By: Relevance
“…Usually a simultaneous induction response in the activities of SOD and CAT is observed when exposed to pollutants that are in agreement with this current study (Dimitrova et al, 1994). The biological importance of CAT are more evident from various studies (Mari et al, 2009) due to the fact that H 2 O 2 is the main cellular precursor of the hydroxyl radical which is a highly reactive and toxic form of ROS (Lopez-Lopez et al, 2011;Mather-Mihaich and Di-Giulio, 1986). The elevated CAT activity in 1/10 th and 1/100 th of SCB and UCB in 7 th day indicated that it could be induced in order to resist the pollutants toxicity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Usually a simultaneous induction response in the activities of SOD and CAT is observed when exposed to pollutants that are in agreement with this current study (Dimitrova et al, 1994). The biological importance of CAT are more evident from various studies (Mari et al, 2009) due to the fact that H 2 O 2 is the main cellular precursor of the hydroxyl radical which is a highly reactive and toxic form of ROS (Lopez-Lopez et al, 2011;Mather-Mihaich and Di-Giulio, 1986). The elevated CAT activity in 1/10 th and 1/100 th of SCB and UCB in 7 th day indicated that it could be induced in order to resist the pollutants toxicity.…”
Section: Discussionsupporting
confidence: 88%
“…Leachate from smoked cigarette filters without tobacco remnants was less toxic than that with tobacco remnants with LC 50 values of 4.1 and 5.5cigarette butts/L respectively for both fish species. Despite the various researches on the toxicity of cigarette butt leachates to various organisms, it is difficult to assess its risk in intricate mixtures of pollutants especially in aquatic ecosystems in diverse manners (Mari et al, 2009).Thus biomarkers, representing toxicant-induced changes in biological systems, can serve as links between an environmental contamination and its effects, providing unique information on the ecosystem health (Lopez-Lopez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This outcome suggests an activation of SOD in Yuriria Lake organisms that could be the result of exposure to xenobiotics, although its increase over the control was not statistically significant. The total IBR value in the gills of the field group (2.45) was double the value of the control group (1.16), indicating that residents of Yuriria Lake face oxidative stress that provokes responses of the antioxidant system (Gül et al, 2004;Iwama et al, 2004;Ferreira et al, 2005; TejedaVera et al, 2006;de la Torre et al, 2007;López-López et al, 2011).Gill histopathology may be indicative of general stress from exposure to various xenobiotics, metals, organic pollutants, toxic algae, and suspended solids (Rendón von Osten). The histopathological changes in this tissue, in general, are a response to exposure to non-specific contaminants (Au, 2004).…”
mentioning
confidence: 98%
“…Furthermore, the overall value of the IBR showed that the field group had a response five times greater (0.21) than that of the control group (0.04). The IBR value in contrast to the individual values of biomarkers show that fish living in Yuriria Lake are facing oxidative stress, which could be attributed to the mixture of pollutants to which these organisms are exposed (Gül et al;Iwama et al;Tejeda-Vera et al;de la Torre et al;López-López et al, 2011).The histopathology of the liver is a general indicator of fish health status as well as of various urban pollutants and toxic levels (Rendón von Osten). Histopathological lesions in the liver usually are not specific to a single pollutant (Au).…”
mentioning
confidence: 99%
“…Another interesting finding for Eriocheir sinensis submitted to acute and chronic exposure to cadmium, was a decrease of the Na + / K + ATPase activity during acute exposure and no effect in chronic exposure 42,43 . In fish, an increase of Na + / K + ATPase was confirmed when some species were exposed chronically to copper (e.g., trout Oncorhynchus mykiss) 44 , or in chronically contaminated environments (e.g., black fin Goodea atripinnis) 45 .…”
Section: Discussionmentioning
confidence: 96%